2004
DOI: 10.2134/jeq2004.1464
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Phosphorus in Surface Runoff and Water Extracts from Semiarid Soils of the Western United States

Abstract: Colloidal particles in runoff may have an important role in P transfer from soils to waterbodies, but remain poorly understood. We investigated colloidal molybdate-reactive phosphorus (MRP) in surface runoff and water extracts of calcareous arable soils from the semiarid western United States. Colloidal MRP was determined by ultrafiltration and operationally defined as MRP associated with particles between 1µm and 1 nm diameter, although a smaller pore-size filter (0.3 nm) was used to define the lower size lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 29 publications
1
35
1
Order By: Relevance
“…1) showed that soil colloids contained hydroxyapatite (HAP), comprising 16.8 and 19.7% of TP coll in the RS and VS, respectively. Turner et al (2004) observed enrichment of both MRP and Ca in colloidal fractions (0.3-3 nm) isolated from calcareous soils; however, the WDCs containing HAP in our study originated from acidic soils. Beauchemin et al (2003) also detected HAP in a range of acidic to slightly alkaline soils using XANES and reported that HAP occurred in all studied soils, regardless of pH.…”
Section: Resultscontrasting
confidence: 81%
See 1 more Smart Citation
“…1) showed that soil colloids contained hydroxyapatite (HAP), comprising 16.8 and 19.7% of TP coll in the RS and VS, respectively. Turner et al (2004) observed enrichment of both MRP and Ca in colloidal fractions (0.3-3 nm) isolated from calcareous soils; however, the WDCs containing HAP in our study originated from acidic soils. Beauchemin et al (2003) also detected HAP in a range of acidic to slightly alkaline soils using XANES and reported that HAP occurred in all studied soils, regardless of pH.…”
Section: Resultscontrasting
confidence: 81%
“…This large distribution of MRP in the colloid fraction further indicates the potential risk of colloid-facilitated MRP losses from soils to water bodies because MRP is regarded as the readily algae-available form in aquatic systems (Van Moorleghem et al, 2013). However, risk assessment of P coll based on MRP coll alone may be misleading because various MRP forms (e.g., mineral phosphate and weakly absorbed phosphate) in colloids act differently in response to environmental changes (Turner et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…The significant amount of CIP observed in the Pearl River likely resulted from the presence of P-containing soil and mineral colloids (Turner et al 2004). Indeed, previous studies have shown a large amount of colloidal orthophosphate in soil surface runoff and soil extract solutions (Sinaj et al 1998; Shand et al 2000; Turner ).…”
Section: Discussionmentioning
confidence: 93%
“…We also observed elevated concentrations of 3-100-kDa colloidal P at enriched sites downstream from agricultural P loading. Colloidal P can include mineral-sorbed P (Al, Fe, and Ca) (Turner et al 2004), humic-metal-phosphate complexes (Hens and Merckx 2001), and extracellular products of microbial metabolism (Paerl and Lean 1976). Colloids can also form suspended particles by self-organizing into 0.4-0.8-mm aggregrates (Kerner et al 2003).…”
Section: Discussionmentioning
confidence: 99%